Nanostructures/Graphene/Silicon Junction‐Based High‐Performance Photodetection Systems: Progress, Challenges, and Future Trends. Issue 7 (29th January 2023) - Iqbal, Muhammad Aamir; Anwar, Nadia; Malik, Maria; Al‐Bahrani, Mohammed; Islam, Md. Rasidul; Choi, Jeong Ryeol; Pham, Phuong V.; Liu, Xiaofeng
Abstract: Graphene, due to its exceptional optoelectronic characteristics, high charge carrier mobility, wide absorption band, strong light‐matter interactions, and its adjustable nature, has attracted a lot of interest. In light of this, an attempt was made to successfully deposit graphene on a silicon substrate. This results in the formation of a Schottky junction, which could extend the operation window of the graphene/silicon hybrid device to the near‐infrared (NIR) region. Furthermore, since photodetectors built with Van der Waal heterostructures successfully extend the lifespan of dynamic charge carriers with improved the transportation range and speed of charge separation for effective photodetection, the technical development of optoelectronic devices has been greatly accelerated. Recent developments in graphene‐silicon junction‐based devices, their photodetection effectiveness, and active factors that can be used in a variety of applications are outlined, including optical synaptic systems, optical spectrometers, plasmonic devices, optical waveguides, and ultrafast photodetectors. Moreover, the shortcomings of the present optoelectronic devices are also concisely reviewed, along with the viable solutions offered by this new device and its application in next‐generation devices. Abstract : This review outlines recent developments in nanomaterials/graphene/silicon junction‐based high‐performance devices, along with their photodetection effectiveness and active factors that can be used in a variety of applications, including optical synaptic systems, optical spectrometers, plasmonic devices, optical waveguides, and ultrafast photodetectors.